1995
DOI: 10.1002/mus.880181112
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of contractile properties between developing and regenerating soleus muscle: Influence of external calcium concentration upon the contractility

Abstract: In newborn rat skeletal extensor digitorum longus (EDL) muscle, it has been found that an influx of calcium from the extracellular medium is necessary for contraction, in contrast to the situation observed in adult EDL muscle. The aim of the present study was to determine the influence of the extracellular calcium concentration ([Ca]o) upon the contractile responses elicited in developing as well as in regenerating (notexin-injected) soleus (SOL) muscle. A morphological study was performed to follow the steps … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

1996
1996
1998
1998

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…Expression of the cardiac isoform of the RyR was not observed. This is the first observation of this kind performed using regenerating skeletal muscle and this finding may contribute to the knowledge of the different mechanisms of EC coupling observed in regenerating versus normal adult skeletal muscle [30,31]. GAPDH expression has been used in the present study as an internal marker, as it is the gene most widely used for that purpose.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Expression of the cardiac isoform of the RyR was not observed. This is the first observation of this kind performed using regenerating skeletal muscle and this finding may contribute to the knowledge of the different mechanisms of EC coupling observed in regenerating versus normal adult skeletal muscle [30,31]. GAPDH expression has been used in the present study as an internal marker, as it is the gene most widely used for that purpose.…”
Section: Discussionmentioning
confidence: 87%
“…However, the mechanisms of EC coupling during skeletal muscle regeneration may be quite different from that in the normal adult. Functional studies have recently shown that, unlike that which is observed to occur in normal skeletal muscle, contraction of skeletal muscle injured by injection of notexin [30] or bupivacaine [31] is strongly dependent on extracellular calcium, as it is in developing skeletal muscle [13,16,39]. These observations suggest that regenerating skeletal muscle exhibits cardiac-like EC coupling.…”
Section: Introductionmentioning
confidence: 97%
“…The preparation was then transferred to the experimental chamber and mounted in the way previously described. 15 Briefly, the two ends of the muscle were carefully snared by fine platinum wire loops, one fixed in the experimental bath and the other to the tip of a force transducer (displacement measuring system Kaman KD 2300, Colorado Spring, CO). Twitches were displayed on an oscilloscope (Tektronix 5115 N, Beaverton, OR) upon stimulation by current pulses (0.5 ms duration, twice the threshold value, frequency 0.07 Hz) applied between two platinum plate electrodes on each side of the channel.…”
Section: Animalsmentioning
confidence: 99%
“…External calcium dependence of the muscle contractility has been demonstrated in the early steps of postnatal development, 7,19 as well as during muscle regeneration, 15,16,18 in contrast to the situation observed in adult skeletal muscle. 8 In postnatal developing and regenerating muscles, neural control could be involved in the dependence of the contractility toward [Ca] o .…”
mentioning
confidence: 98%
See 1 more Smart Citation